Multi-targeted metagenetic analysis of the influence of climate and environmental parameters on soil microbial communities along an elevational gradient - Lanzén, Anders (Sci Rep, 2016)
Mountain elevation gradients are invaluable sites for understanding the effects of climate change on ecosystem function, community structure and distribution. However, relatively little is known about the impact on soil microbial communities, in spite of their importance for the functioning of the soil ecosystem. Previous studies of microbial diversity along elevational gradients were often limited by confounding variables such as vegetation, pH, and nutrients. Here, we utilised a transect in the Pyrenees established to minimise variation in such parameters, to examine prokaryotic, fungal, protist and metazoan communities throughout three consecutive years. We aimed to determine the influences of climate and environmental parameters on soil microbial community structure; as well as on the relationships between those microbial communities. Further, functional diversity of heterotrophic bacteria was determined using Biolog. Prokaryotic and fungal community structure, but not alpha-diversity, correlated significantly with elevation. However, carbon-to-nitrogen ratio and pH appeared to affect prokaryotic and protist communities more strongly. Both community structure and physicochemical parameters varied considerably between years, illustrating the value of long-term monitoring of the dynamic processes controlling the soil ecosystem. Our study also illustrates both the challenges and strengths of using microbial communities as indicators of potential impacts of climate change.